Elucidating hard coral community in tropical coral reefs of Pulau Bidong and nearby islands, South China Sea - MOHMAD FUAD NUR QAMARINA; WEE HIN BOO; YU HAI PING; ZAINUDIN BACHOK; CHE DIN MOHD SAFUAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Qamarina MFN, Boo WH, Ping YH, Bachok Z, Safuan CDM. 2025. Elucidating hard coral community in tropical coral reefs of Pulau Bidong and nearby islands, South China Sea. Biodiversitas 26: 444-457. This study investigates the intricate dynamics of hard coral communities within the tropical coral reefs of the South China Sea, a region renowned for its high marine biodiversity. Data were collected through video sampling to assess the hard coral composition around Pulau Bidong and nearby islands, analyzing variations of hard coral communities across different variables such as island, depth, habitat, and exposure. In total, 40 hard coral genera from 15 families were identified in the study area. Overall, Acropora (22.41% ± 22.17) emerged as the most prominent genus, followed by Porites (5.8% ± 10.27). Acropora dominated in leeward reefs (28.70% ± 22.84) and sandy habitats (29.11% ± 23.89), both sheltered from intense winds and currents. Porites were abundant in exposed reefs (13.69% ± 16.4) with submerged habitats (35.64% ± 8.42) and windward reefs (9.33% ± 10.47) with rocky habitats (8.17% ± 9.46), both of which are subject to higher physical disturbances. Varying local conditions significantly influence the composition of hard coral communities in these tropical reefs. These findings underscore the urgent need for conservation in disturbed reefs, as they should be protected from intense human activities to preserve hard coral diversity. The recommendation that sheltered areas, such as leeward reefs, may be more suitable for water activities and controlled human development supports the responsible utilization of Pulau Bidong and nearby islands while ensuring the long-term sustainability of the marine ecosystem. Overall, this study provides a foundational understanding of how local environmental variables affect hard coral communities in the South China Sea, a crucial insight for developing effective coral reef management strategies amid increasing pressures from climate change.